Congelamento ultra-rápido de embriões bovinos com etilenoglicol e trealose - Almeida, Nezinho Ventura de (2001)
Embryo cryopreservation is a procedure widely employed in the domestic animal assisted reproduction and is highly representative in the bovine species, as seen in North America were over 40% of collected embryos are frozen using the conventional method. In contrast with the advances in biotechnology, the equipment available in the market is very expensive. In order to reduce costs and time necessary for freezing, the present study evaluated the effect of ethylene glycol associated with trehalose on bovine embryos produced in vivo. Embryos were frozen by ultra-rapid method that does not involve the use of high cost equipment. The low molecular weight of ethylene glycol results in higher permeability and lower toxicity. It´s association with trehalose in adequate concentration reduces freezing time with rapid and direct exposure of the straw containing the embryo to liquid nitrogen. Ninety one (n=91) in vivo produced bovine embryos were frozen by the ultra-rapid method using ethylene glycol and trehalose and by the conventional method. The embryos were randomly distributed in two experiments with three treatments each. In experiment I, embryos frozen by the ultra rapid method were exposed for 2 minutes to liquid nitrogen vapour before they were plunged into liquid nitrogen. Twenty-nine embryos were exposed to 2.0M ethylene glycol + 0.3M trehalose and PBS + 0.4% BSA (T1), 24 were exposed to 3.0M ethylene glycol + 0.3M trehalose in PBS + 0.4% BSA (T2) and 19 were frozen by the conventional method with 1.5M ethylene glycol in Emcare solution (T3 = control). In the second experiment embryos were exposed to identical solutions and treatments however they remained just for 20 seconds in liquid nitrogen vapor. Seven embryos were exposed to 2.0M ethylene glycol + 0.3M of trehalose in PBS + 0.4% BSA (T1), 5 to 3.0M Ethylene Glycol + 0.3M trehalose in PBS + 0.4% BSA (T2) and 7 were frozen by the conventional method using 1.5M ethylene glycol in Emcare (T3 = control). After thawing, all embryos were transferred to previously synchronized recipients resulting in a pregnancy rate of 17%, 13% and 37% in T1, T2, T3, respectively at 45 days, in experiment I. The pregnancy rate in experiment II was 14% for T1, 40% for T2 and 43% for T3. No significant difference was detected between treatments (P>0.05). Trehalose was efficient for the ultra-rapid freezing of bovine embryos to be used for direct transfer. The association of ethylene glycol 3.0M with trehalose 0.3M for ultra-rapid freezing of bovine embryos and the exposure to liquid nitrogen for twenty seconds resulted in promising perspectives for this methodology in the bovine species.